Locating the Mobile Producer’s Position in Wireless NDN Environment using Signal Strength - Zaharadeen Ahmed, Muhammed; Hassan Abdalla Hashim, Aisha; Omran Khalifa, Othman; Hammawa Song, Ahmed; Hamidu Alkali, Abdulkadir; A. Hamida, Belal (International Journal on Perceptive and Cognitive Computing, 2021)
This paper assesses the Muslim contribution in Computer Science Applications and Technology. This involve in-depth analysis of recent technologies in computer, based on perspective that Islam accommodates. All research conducted from the history of civilization is basically driven from script of the Quran and Sunnah. Therefore, technology and science are derivatives of Islamic civilization. Recent technology of the Internet is now centred on multimedia contents applications (such as audio, video and images). This is due to the rapid innovations and production of electronic devices across the globe. The idea of contents on the Internet is developed from the Content Concentric Network (CCN). And the most promising between CCN types is the Named Data Networking (NDN). Named Data Networking is a new content centric network architecture that can possibly overwhelm most issues of IP mobility and security. NDN approach is commonly identified under Information Concentric Network or Content Concentric Network and is centered on addressing contents by themselves using names, rather than assigning IP addresses to packets on hosts, where information is located on the global Internet. Due to the developing scope of remote access around the world and Wi-Fi accessibility, scenarios change as a result of additional networking devices. This paper also analyses existing methodologies of mobile device communication using Wi-Fi in NDN environment. This involves using a mobile producer and a rendezvous node connected via content routers in a network. Their location is detected and predicted immediately handoff occur and it transmit content as a consumer. The approach of transmitting content signals uses sign power pointer, Received Signal Strength Indicator (RSSI), Time of Arrival (TOA) and TSE in the network. Several challenges were noted and pointed out o enhance future work.